Pengaruh Tingkat Kesadaran Keluarga Muda Mengenai Perencanaan Keuangan Keluarga Terhadap Family Financial Distress (Studi Kasus di Kecamatan Banyuwangi) - Ike Meilani Fajarsari; Yayan Ananto; Mainike Silvi Rety Badian (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The economic crisis can impact family stability, including financial pressures that often lead to divorce. Data from the Indonesian Badan Pusat Statistik (2024) indicate that although the divorce rate has decreased in recent years, economic issues remain one of the primary causes of marital breakdown. Managing household finances, especially among young couples, has become increasingly complex due to changing lifestyles and rising living costs. This study aims to analyze the role of financial planning in reducing family financial distress, focusing on financial literacy, financial inclusion, financial attitudes, and employment status. The research was conducted in Banyuwangi District using a quantitative approach with multiple linear regression analysis. Data were collected from 393 respondents using questionnaires. The results indicate that financial inclusion, financial attitudes, financial literacy, and employment status significantly influence family financial distress. Financial inclusion has the most significant impact, followed by financial attitudes, financial literacy, and employment status. The R Square value of 0,582 suggests that 58,2% of the variability in family financial distress can be explained by these variables. These findings highlight the necessity of proper financial planning to enhance family well-being and reduce economic pressures that may lead to household conflicts. This study emphasizes the importance of raising public awareness, particularly among young couples, about effective financial planning. The government and financial institutions are also expected to play an active role in providing financial education and improved access to financial services. With proper financial planning, families can achieve greater economic stability and minimize the risk of financial distress, which could affect household harmony.